Economy and Literature: by the light of asian, european narrators and Peruvians - Armas Morales, Carlos (2017)
The article tries to show the presence of the economy through the bibliographical investigation of literary works (you novelize and stories) of Japanese, French authors and Peruvians; in the possibility of knowing some relationships of the economy and the narrative one and also to observe the utility of the reading of these works like supplement in the teaching of some matters of economy (national reality, economic right, economic history of the country etc.) of conformity with the results of the author’s investigation.